Multidetector computed tomography imaging of squamous cell carcinoma of buccal mucosa - Sankhe, Ashwini; Rahatekar, Neha; Mankar, Diksha (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
This study aims at describing the role of multidetector computed tomography (MDCT) and CT imaging findings in evaluation of squamous cell carcinoma of buccal mucosa and its staging. Retrospective study of 40 patients who underwent MDCT and were histopathogically proven case of squamous cell carcinoma (SCC) of buccal mucosa patients were included in the study. Plain, arterial, venous phase and puff cheek CT cuts were taken from base of skull till clavicle. The imaging findings in squamous cell carcinoma (SCC) of the oral cavity allow the radiologist to accurately determine the extent and staging of disease thereby help clinicians plan appropriate treatment. 40 such patients were done in which majority of them are male patients-27 as compared to female patients-13. Among these 40 patients, 20 patients had stage IVB cancer, 13 patients had stage IVA, 5 patients had stage II and 2 patients had stage I cancer. No patient included in our study had stage III. Patients’ recovery will depend on how early the cancer is found and staging gives an idea of patients’ possible outcomes. MDCT is non-invasive and cost-effective investigation which helps in evaluating squamous cell carcinoma of buccal mucosa and determines its stage of buccal cancer and guide the therapy accordingly.